P44 Using simulation as a tool to improve health practitioner knowledge, skills and confidence in delivering safer care to acutely unwell patients. (3rd November 2019) - Williamson, Sarah; Fullwood, Isobel; Bradshaw, Jane; Elson, Ross; Wang, Justin; Neal, Richard; Nash, Abigail
Abstract : Background: Simulation facilitates multidisciplinary teams (MDT) encountering patient emergencies to reflect and learn from critical incidents in a safe, reproducible environment. This can improve knowledge, skills and confidence to delivery safer care to acutely unwell patients. It is therefore essential that this is offered regularly to all health care practitioners. Our aim was to implement a MDT point of care simulation programme at a tertiary Children's Hospital, assessing acutely unwell children outside of the paediatric intensive care unit environment. Summary of work: Since February 2019 we have designed and implemented a bimonthly medium fidelity point of care simulation programme, available to all health practitioners. Prior to this simulation training at the hospital was carried out on an adhoc basis. We have successfully delivered eight one hour sessions; three cardiac arrest and five deteriorating ward inpatient scenarios followed by supportive debrief using the diamond debrief model. This has been led by a team of PICU consultants, nurse educators and a simulation fellow. Themes obtained from monthly safety team incident reviews via NHS incident reporting system, have been incorporated into the scenario design. Summary of results: Fifty one health care practitioners have volunteered to take part in the simulation scenarios, on seven different wards. Feedback was obtained using anonymous post sessions questionnaires. Likert scales were used to ascertained staff confidence pre and post training. 98% (n=50) of participants reported that they found the scenarios useful and 90% (n=46) agreed they felt more confident to deal with this scenario in the future. Key technical learning points reported include the administration of adrenaline during cardiac arrest, performing the ABCDE assessment and setting up equipment e.g. high flow oxygen. Key non-technical skills reported include effective communication, the use of the SBAR handover tool during escalation, team work and confidence to speak up in an emergency. Discussion and conclusions: Point of care simulation offers health practitioners a safe learning opportunity to enhance knowledge, skills and confidence in emergency situations. We aim to continue to delivery regular point of care simulation training, specific to individual ward needs.